2003
DOI: 10.1128/jvi.77.18.9823-9830.2003
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Immunization with Virus-Like Particles of Simian Immunodeficiency Virus Conjugated with Cholera Toxin Subunit B

Abstract: To enhance the efficiency of antigen uptake at mucosal surfaces, CTB was conjugated to simian immunodeficiency virus (SIV) virus-like particles (VLPs). We characterized the immune responses to the Env and Gag proteins after intranasal administration. Intranasal immunization with a mixture of VLPs and CTB as an adjuvant elicited higher levels of SIV gp160-specific immunoglobulin G (IgG) in sera and IgA in mucosae, including saliva, vaginal-wash samples, lung, and intestine, as well as a higher level of neutrali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 54 publications
2
25
0
Order By: Relevance
“…It has been reported that CTB induces a high titer of IgA antibody to HIV-1 (Bukawa et al, 1995;Kang et al, 2003) and IgG antibodies are induced less efficiently (Kim et al, 2004), like our results the IgG in serum were not significant as compared to IgA antibodies production.…”
Section: Discussionsupporting
confidence: 63%
“…It has been reported that CTB induces a high titer of IgA antibody to HIV-1 (Bukawa et al, 1995;Kang et al, 2003) and IgG antibodies are induced less efficiently (Kim et al, 2004), like our results the IgG in serum were not significant as compared to IgA antibodies production.…”
Section: Discussionsupporting
confidence: 63%
“…Similar phenomena have been observed with other pathogen-associated molecular patterns related to their corresponding TLRs. Previous studies showed that simian immunodeficiency virus VLPs conjugated with cholera toxin subunit B induced humoral and cellular responses that were stronger than those seen for a mixture of toxin with VLPs (21). It was also reported that when CpG-DNA is linked to ovalbumin, the protein uptake is facilitated by a receptor-mediated mechanism (50).…”
Section: Discussionmentioning
confidence: 99%
“…III). However, it is interesting to note that the holotoxin stimulates stronger responses on a dose-bydose basis following intranasal delivery compared to the B subunit [52,108].…”
Section: Ct-b and Lt-bmentioning
confidence: 99%